Chemical and sensory profiling of Shiraz wines co‐fermented with commercial non‐Saccharomyces inocula. (28th December 2017) - Hranilovic, A.; Li, S.; Boss, P.K.; Bindon, K.; Ristic, R.; Grbin, P. R.; Van der Westhuizen, T.; Jiranek, V.
Abstract: Background and Aims: The choice of yeast strain(s) to conduct the fermentation can greatly affect wine chemical and sensory profile. Even though the use of non‐ Saccharomyces co‐inocula to build complexity and diversify styles is increasingly in vogue, a limited number of such products are available to date, and more research is required to guide their use in the wine industry. This study evaluates the potential of commercial yeast inocula to modulate the quality of Shiraz wines at two maturity levels. Methods and Results: Vinification outcomes of eight yeast treatments were compared in earlier (24°Brix) and later (29°Brix) harvested Shiraz fruit. Yeast treatments included five non‐ Saccharomyces products with sequentially inoculated Saccharomyces cerevisiae, a commercial blend of non‐ Saccharomyces and S. cerevisiae strains, and a S. cerevisiae inoculum. Fermentation monitoring, and comprehensive analytical profiling in terms of basic chemistry, volatile composition, phenolic measurements and descriptive sensory analysis, allowed for the comparison of the resulting wines. Both harvest date and yeast inoculation treatments had a significant impact on a range of compositional and, in turn, sensory parameters of the wines. Conclusions: Certain non‐ Saccharomyces sequential inoculation treatments led to increased appeal of earlier harvest wines compared to the S. cerevisiae Control. These treatments, however, were related to an increased risk of arrested fermentation in higher ripeness conditions. Significance of the Study: This study contributes to a better understanding of yeast inoculum‐derived modulation of Shiraz wine quality parameters at different maturity levels.